The use of various types of hip prostheses depending on the patient’s age and level of everyday activity - Poboży, Tomasz; Kielar, Maciej (Medical Studies/Studia Medyczne, 2015)
Hip replacement surgery is becoming more and more common in clinical practice, as a growing number of patients qualify to receive this form of treatment. This is because the aging of the society, high prevalence of overweight, and little physical activity contribute to the development of osteoarthritis. Moreover, patients have come to expect good quality of life even at advanced age. Thanks to progress in surgical techniques, these expectations can now be met. Endoprosthesis selection – apart from medical indications – must be based on the patient’s age, everyday activity, and further plans. There are two main types of clinical situations where hip arthroplasty is performed; these are hip joint degeneration and femoral neck fracture. This article aims to present current options of total hip replacement to healthcare professionals who wish to learn more on the subject, including physical therapists, nurses, and professional caretakers for patients with walking difficulties.